Bimetallic Pt–Au nanoparticles supported on multi-wall carbon nanotubes as electrocatalysts for oxygen reduction. (March 2016) - Félix-Navarro, R.M.; Beltrán-Gastélum, M.; Reynoso-Soto, E.A.; Paraguay-Delgado, F.; Alonso-Nuñez, G.; Flores-Hernández, J.R.
Abstract: Platinum-gold nanoparticles supported on multi-wall carbon nanotubes (MWCNT) with various Pt:Au ratios are prepared by microemulsion method for use as electrocatalysts in the oxygen reduction reaction (ORR). The influence of the Pt:Au ratio on the electrocatalytic activity during ORR is investigated in detail. The synthesized nanomaterials are analyzed by different physicochemical techniques. The electrocatalytic activity for oxygen reduction is evaluated using a rotating disk electrode (RDE) system. We report that the activity and oxygen reduction mechanism depends strongly on the Pt:Au ratio; in the case of Pt:Au ratio higher than 0.60, oxygen is reduced to water by a four electron process pathway, while at 0.33 ratio the reaction follows a two-electron-transfer mechanism. Highlights: Six catalyst based Pt–Au on MWCNT were synthetized to carry out oxygen reduction. Electrochemical techniques were employed to determinate the ORR performance. Electrocatalysts were studied for ORR in presence and absence of methanol. Pt:Au(10:10)/MWCNT showed the highest catalytic activity to oxygen reduction. ORR occurs by four electrons pathway in all catalyst, except Pt:Au(05:15)/MWCNT.